Peranan Bagian Kebersihan Kecamatan Lubuk Pakam dalam Meraih Adipura - Malem, Surung; Dewi, Rosmala; Lubis, Yurial Arif (Universitas Medan Area, 2016)
Lubukpakam city as one of the participants of the small town, which managed to achieve and maintain adipura 6 (six) consecutive times including in 2013. This program is the development of adipura (1986-1997), which had been halted because of the economic crisis, because the conditions of urban environment tends to decrease since the termination of the program in 1997, after about five (5) years of stalled chart shows a decrease in the level of cleanliness quite dramatically between the cities participants. Issues raised in this study were: (1) lack of attention to the current Subdistrict Section Adipura Cleanliness obtained a city; (2) The role of the District Cleanliness is part of the cutting edge in getting Adipura lack of facilities and infrastructure in cleanliness; (3) Lack of cooperation provided by the community in efforts to improve environmental hygiene. The results of this study indicate that in order to maintain the cleanliness of the environment must be equipped with a high awareness within the community without waiting Verse, do not clean city solely to maintain the cleanliness of the environment, but it is clean city as an effort to maintain the cleanliness and aesthetics which we galakkan because cleanliness is part of faith. So with the clean city is a motivation to raise public awareness in keeping the environment respectively.